Firm strategy and CSR: the moderating role of performance management systems. (3rd January 2022) - Galbreath, Jeremy; Lucianetti, Lorenzo; Tisch, Daniel; Thomas, Benjamin
Abstract: Little empirical research has explored whether or not firm strategy is linked with corporate social responsibility (CSR) and to that end we explore the impact of low-cost and differentiation strategies on CSR. Using a sample of 229 Italian firms, a low-cost strategy is negatively associated with ethical and discretionary CSR, while a differentiation strategy is positively associated with both. Given its focus on nonfinancial outcomes and stakeholders, we test if a performance management system (PM system) acts as a moderating influence. We find that a PM system positively moderates the negative association between a low-cost strategy and ethical and discretionary CSR, while also positively moderating these relationships with respect to a differentiation strategy. These findings advance the literature on strategy and CSR, while demonstrating the contingent effect of PM systems. The findings are discussed along with limitations and directions for future research.